2022
DOI: 10.3390/jcm11051218
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological and Interactive-Relational Characteristics in Non-Suicidal Self-Injury Adolescent Outpatients

Abstract: Non-suicidal self-injury (NSSI) is described as behaviors that directly and intentionally inflict damage to body tissue without suicidal intent and for reasons not linked to cultural expectations or norms. Literature has confirmed several “specific risk factors” related to NSSI behaviors; emotional reactivity, internalizing problems, alexithymia traits, and maladaptive family functioning can predispose an individual to intrapersonal and interpersonal vulnerabilities related to difficulties in regulating one’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We demonstrated that family functioning differs between adolescents with and without NSSI. A study showed that poor family communication and lack of support may promote the development of NSSI, which in turn affects the relationship between children and parents and damages family function, forming a vicious circle ( 44 , 45 ). The specific role of the familial environment in the occurrence of NSSI needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that family functioning differs between adolescents with and without NSSI. A study showed that poor family communication and lack of support may promote the development of NSSI, which in turn affects the relationship between children and parents and damages family function, forming a vicious circle ( 44 , 45 ). The specific role of the familial environment in the occurrence of NSSI needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit, with these limitations, our findings can provide useful theoretical-clinical input, and entitle us to claim that a combination of alexithymia and somatization in selfharming patients is associated with more severe clinical picture. Investigating these aspects in patients who engage in self-harming, both clinically and with the aid of tests-and possibly taking into account the environment in which patients live and the dynamics of their family interactions [45,53,54]-could help us to identify the individuals at greater psychopathological risk. This is an interesting finding from a preventive and intervention perspective, suggesting the importance of work on emotional awareness, on the capacity to recognize and express feelings to acquire competence in their regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities of emotional perception and regulation in nonsuicidal self-injury ED is a transdiagnostic construct defined as the inability to regulate the intensity and quality of emotions (eg, sadness, anger, or fear) to generate an appropriate emotional response, cope with mood instability and emotional overactivity, and return to the emotional baseline 26 . Previously published studies showed that NSSI was associated with difficulty in emotional perception, emotional overactivity, and emotion regulation [27][28][29][30][31] . For example, individuals engaged in NSSI struggled with perceiving their emotions and expressing them to others through interpersonal communication.…”
Section: Nonsuicidal Self-injury and Emotional Dysregulationmentioning
confidence: 99%
“…For example, individuals engaged in NSSI struggled with perceiving their emotions and expressing them to others through interpersonal communication. Consequently, they often used their bodies as a tool for communicating their emotions 27,28 . Another study found that adolescents with NSSI demonstrated lower accuracy in recognizing facial expressions of fear and sadness compared with adolescents without a history of NSSI 29 .…”
Section: Nonsuicidal Self-injury and Emotional Dysregulationmentioning
confidence: 99%